JUNE 27 HEARINGS ON LEGISLATION TO RESTRICT SMOKING IN FEDERAL BUILDINGS (Tufts Archival Research Center, 2007)
Duplicate; Memorandum from Sam Chilcote to members of Tobacco Institute Executive Committee on the June 27 Congressional Subcommittee Hearings on restricting smoking in federal buildings. Summarizes the testimony of 13 witnesses before Subcommittee on Health and the Environment. Discusses issues of ventilation and clean indoor air and nonsmokers rights. Includes testimony by government health officials, citizens interest groups and labor groups.